(untitled) (Scientific journal of the Fergana State University, 2026)
The article scientifically analyzes the factors of formation of the Jadid movement in Turkestan in the late 19th and early 20th centuries, its ideological foundations, educational and political directions, main representatives, and the impact of the movement on the development of society. It also comprehensively covers the regional characteristics of Jadidism, the process of its emergence in the conditions of colonial Turkestan, and its role in national revival.